The The Jigsaw Model Strategy As A Peer-Teaching Method In Islamic Education Subjects - Rihadatul Aisy, Salwa; Syahidin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The Jigsaw Model, which emphasizes collaboration among students, provides an opportunity for them to become